Indications, preferences, global practice patterns and outcomes in retrograde intrarenal surgery (RIRS) for renal stones in adults: results from a multicenter database of 6669 patients of the global FLEXible ureteroscopy Outcomes Registry (FLEXOR). - TANIDIR, YILÖREN (My University, 2022)
Purpose To collect a multicentric database on behalf of TOWER research group to assess practice patterns and outcomes of retrograde intrarenal surgery (RIRS) for kidney stones. Methods Inclusion criteria: age≥18 years, normal renal/calyceal system anatomy, calculi of any size, number, and position. Study period: January 2018 and August 2021. Stone-free status: absence of fragments>2 mm, assessed post procedure according to the local protocol (KUB X-Ray and/or ultrasound or non-contrast CT scan). Results Twenty centers from ffteen countries enrolled 6669 patients. There were 4407 (66.2%) men. Mean age was 49.3±15.59 years. Pain was the most frequent symptom indication for intervention (62.6%). 679 (10.2%) patients underwent RIRS for an incidental fnding of stones. 2732 (41.0%) patients had multiple stones. Mean stone size was 10.04±6.84 mm. A reusable fexible ureteroscope was used in 4803 (72.0%) procedures. A sheath-less RIRS was performed in 454 (6.8%) cases. Holmium:YAG laser was used in 4878 (73.1%) cases. A combination of dusting and fragmentation was the most common lithotripsy mode performed (64.3%). Mean operation time was 62.40±17.76 min. 119 (1.8%) patients had an intraoperative injury of the ureter due to UAS insertion. Mean postoperative stay was 3.62±3.47 days. At least one postoperative complication occurred in 535 (8.0%) patients. Sepsis requiring intensive care admission occurred in 84 (1.3%) patients. Residual fragments were detected in 1445 (21.7%) patients. Among the latter, 744 (51.5%) patients required a further intervention. Conclusion Our database contributes real-world data to support to a better understanding of modern RIRS practice and outcomes.
Keywords: Kidney calculi; Flexible ureteroscopy; Retrograde intrarenal surgery; Lithotripsy; Laser